Quantitative Trait Loci Influencing Mycotoxin Contamination of Maize: Analysis by Linkage Mapping, Characterization of Near‐Isogenic Lines, and Meta‐Analysis. Issue 1 (1st January 2014) - Mideros, Santiago X.; Warburton, Marilyn L.; Jamann, Tiffany M.; Windham, Gary L.; Williams, W. Paul; Nelson, Rebecca J.
ABSTRACT: Mycotoxin contamination of maize ( Zea mays L.) exposes people to grave health consequences in subsistence agricultural settings and to economical losses in quality‐regulated markets. Genetic variation for resistance to aflatoxin accumulation in maize has been reported in many studies. Resistance can act at multiple steps at which there is fungal–plant interaction. In this study, we report the identification and mapping of quantitative trait loci (QTL) for multiple traits or components of resistance to Aspergillus flavus using different genetic tools and resources. For QTL mapping, we used a B73 × CML322 population of recombinant inbred lines. Ten QTL were found using two QTL mapping methods, six of which were located on the same chromosome segments using both approaches. These QTL were located in maize bins 4.08, 4.09, 8.02, 8.03, 10.06 and 10.07. Various sources of near‐isogenic lines (NILs) for selected loci were tested. The resistance QTL located in bin 4.08 was confirmed using a NIL pair. Finally, we conducted a meta‐analysis of QTL using data from 12 populations in which resistance to Aspergillus, Fusarium, or Giberella ear rots has been mapped. This meta‐analysis indicated that the QTL in bin 4.08 has been reported in four mapping populations. Overall, we found evidence for significant QTL × year interactions and that QTL were distributed in a manner consistent with an infinitesimal model. The largest‐effect QTL, located in bin 4.08, is a good candidate for further characterization and use.